FACING THE GLOBAL WORLD OF WORK: CURRICULUM TRANSFORMATION THAT ALIGNS HARD SKILLS AND SOFT SKILLS - Yogi, Chatreys Suci Ramadani; Aimah, Siti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Curriculum transformation that harmonizes the development of hard and soft skills is a strategic step in preparing individuals to face the demands of the global workforce. Hard skills, such as technical and analytical abilities, are needed to master specific jobs, while soft skills, such as communication, teamwork and adaptability, are key to success in a dynamic and collaborative work environment. This research aims to explore the principles, challenges and strategies of curriculum transformation that can integrate both types of skills in a balanced way. Through literature analysis and case studies, it was found that collaboration between educational institutions, industry and society is essential in creating a relevant and applicable curriculum. This transformational curriculum produces graduates who are not only technically competent, but also have strong interpersonal skills, making them ready to compete in the global job market. The results of this study contribute to the development of an inclusive and sustainable education model.